Cocooning strategy: Pertussis vaccination coverage rate of parents with a new-born in 2016 and 2017 in France - Marchal, Clarisse; Belhassen, Manon; Guiso, Nicole; Jacoud, Flore; Cohen, Robert; Le Pannerer, Marie; Verdier, Régis (Frontiers in Pediatrics, 2022)
Background: The “cocooning” strategy was introduced in 2004 to protect infants too young to be vaccinated against pertussis, by immunizing their parents and close relatives. The study objective was to assess its implementation 12 years after its introduction by estimating the pertussis vaccination coverage rates (VCR) among parents of newborns. Methods: Pertussis VCR were estimated among all women who gave birth and men who took paternity leave, in 2016 or 2017, from a 1/97th random sample of French claims data. Two distinct study periods were defined based on current recommendations for the cocooning strategy: the “common practice” and the “parental project” periods. Results In 2016, the pertussis VCR of women having given birth and men having taken paternity leave was 47.2% and 47.1%, respectively (46.1% and 45.6% in 2017 respectively). About one quarter of vaccinations were performed during the “parental project” period, with the vaccine most frequently reimbursed during the month of childbirth for women (57.1% in 2016 and 49.4% in 2017) and before or during the month the paternity leave began for men (about 78% in both 2016 and 2017). General practitioners were the main prescribers in private practice, even during the “parental project” period. Conclusion: To optimize the protection for infants, the main objective of the cocooning strategy, pertussis immunization coverage of adults and seniors needs to be improved. Moreover, cocooning vaccination linked to a parental project needs to be performed earlier, during pregnancy (for those around the mother) or in immediate post-partum (e.g. during the maternity stay).